APT - evidencia empírica en el análisis del ROA en una empresa de servicios públicos domiciliarios de acueducto y alcantarillado (2014)
Using methodology developed by ROSS, the Return on Assets - ROA was assessed for a firm of public utilities for water and sewer department of Antioquia. The public utilities sector of water is monopolistic nature and the method of valuation of the cost of capital used to determine the rates of the companies involved in this, is regulated by an agency of Colombia. This paper evaluates a different or complementary alternative to the CAPM method used by the regulator to find the cost of capital that reflects the characteristics of this market in Colombia. For achieving this goal, in this paper the method of principal components is incorporated, reducing 19 observed variables that are classified into various categories: macroeconomic, financial, technical and operating of the company studied. From the data, it was established the results achieved in five components that determine the profitability of the assets of the company analyzed, highlighting the geographical coverage and operational performance.